Fulminant Herpes Pneumonia Postaortic Surgery with Known Ankylosing Spondylitis - Asemota, Nicole; Ike, Ikenna David; Oo, Aung Ye; Lopez-Marco, Ana (AORTA, 2022)
Herpes simplex virus (HSV) pneumonitis is rare after cardiac surgery. A 36-year-old gentleman with ankylosing spondylitis underwent emergency surgery for a complex aortic aneurysmal disease. Preoperative treatment of aortitis with antitumor necrosis factor and steroid medication and surgical stress including cardiopulmonary bypass potentially created an immunosuppressive state and reactivation of undiagnosed HSV. Rapid HSV pneumonia ensued, culminating in fulminant organ failure and mortality. HSV pneumonia should be considered postoperatively in patients with severe respiratory distress, especially if immunocompromised.
Keywords: pneumonia; herpes simplex; postoperative; immunosuppression